Penguatan Ideologi Pancasila Sebagai Penangkal Radikalisme Agama - Yakobus Adi Saingo (Undiksha, 2022)
This study will discuss the strengthening of Pancasila ideology as an antidote to religious radicalism that is able to threaten the unity dan integrity of the Indonesian nation. This study aims to describe that Pancasila is the fundamental ideological foundation of every Indonesian society against the problems of religious radicalism that disturbs the beauty of diversity that has existed in the midst of the Indonesian nation so far. As the basis of the state philosophy, the ideology of Pancasila is contrary to the notion of religious radicalism because it can undermine the unity dan integrity of the nation. The literature study method used in this research is to describe the general picture of the problems experienced by the Indonesian people regarding religious radicalism, which also systematically proposes efforts to counteract the dangers of religious radicalism through strengthening the ideology of Pancasila. Sources of data will be taken from the majority of scientific journals published in the last 7 (seven) years as well as supporting books related to the discussion theme. How to obtain these data is by researchers conducting research dan literacy approaches that are relevant to the research theme. The data will be analyzed in depth by the researchers so that they are able to describe the general picture regarding the problems of religious radicalism experienced by the Indonesian people, as well as the solution through strengthening the ideology of Pancasila. Thus, strengthening the Pancasila ideology as an antidote to religious radicalism is expected to be a solution in establishing the unity dan integrity of the Indonesian nation.